Post Tension Losses: A comparative study of different codes of practice - Tolba, Hana Moataz (AUC Knowledge Fountain, 2026)
Pre-stressed post-tensioned concrete has become a cornerstone of contemporary structural design due to its ability to enhance load-bearing capacity, minimize deflections, and extend span lengths efficiently. Accurate estimation of pre-stress losses is essential for ensuring structural reliability and serviceability over the lifespan of such systems. This study presents a comprehensive evaluation of initial and long-term pre-stress losses in post-tensioned concrete elements, applying and comparing provisions from four major international design codes: The Egyptian Code for Design and Construction of Concrete Structures (ECP 203-2007), the American Concrete Institute's ACI 423.10R-16, Euro code 2, and the Canadian CSA A23.3 standards as detailed in the CPCI Design Manual (5th Edition). This thesis contributes to the field of structural engineering by offering a detailed comparative framework for pre-stress loss across three distinct beams. It not only bridges gap in current literature but also offers recommendations for future code enhancements and standardization efforts. Ultimately, the findings aim to improve the fidelity of pre-stressed concrete design, fostering greater structural efficiency, safety, and economy in modern construction. The research numerically investigates three post-tensioned concrete beams with varying geometrical and pre-stressing parameters, including jacking force magnitudes, strand arrangements, and span lengths. For each beam, initial losses—comprising elastic shortening, friction, and anchorage slip—are calculated in accordance with each code's methodology. Long- term losses due to creep, shrinkage, and steel relaxation are similarly quantified. Euro code 2 is distinct in its integration of all time-dependent losses into a single expression, whereas the other codes treat each component individually, leading to variances in the magnitude and behavior of calculated losses. One of the study’s key contributions lies in examining the applicability of a new equation developed by Mostafa Serry, which refines friction loss estimations based on full-scale experimental data. By applying this equation to different case scenarios, the study assesses its impact on enhancing the accuracy of initial loss predictions. Numerical analysis revealed consistent trends in loss behavior across codes, yet significant quantitative disparities were observed, stemming from differences in material properties, empirical coefficients, and modeling assumptions. These discrepancies underline the importance of selecting a code that aligns with both regional construction practices and the structural requirements of a given project. Furthermore, the study highlights the sensitivity of pre-stress loss estimations to beam-specific parameters, emphasizing the necessity for case-specific evaluation in practical design.